GOVERNMENT RESPONSIVITY THROUGH ELECTRONIC GOVERNMENT (E-GOV) IN MAKASSAR CITY - Nur Pratiwi, Oky; Nahruddin, Zulfan; Nur Aina, Asri; Arifin, Indar (Jurnal Administrasi Negara, 2023)
The purpose of this study is to determine government responsiveness through electronic government (e-gov) in the city of Makassar. Electronic Government in this research is the use of information and communication technology as a tool by the government in order to provide effective and fast services to the community. This research uses a descriptive-qualitative method. The results of the study show that all people can enjoy these services without exception. The Makassar City Communication and Information Service has provided competent employees so they can carry out their duties and functions properly. The government, as a public servant, is obliged to serve the community well and in accordance with its needs. Diskominfo provides services that are fast, good at responding to community needs, easy, and practical. The Ministry of Communications and Informatics has provided accurate information regarding the city of Makassar, as well as providing information in a transparent and reliable manner to the public without discrimination.